FAKTOR-FAKTOR YANG MEMPENGARUHI PSIKIS IBU BERSALIN POSITIF COVID-19 DI RSUD R.A.A TJOKRONEGORO PURWOREJO - Ika Zuliyanti, Nurma; Bertina Desta Merta Vitanisa, Puja (Jurnal Komunikasi Kesehatan, 2023)
From the medical records of patients who gave birth positive from covid-19 at R.A.A Tjokronegoro Hospital purworejo, 142 mothers who gave birth were positive for covid-19 and 40 of them were pshycoloically disturbed. To find out the factors affecting the psychic of the mother who is positive for covid-19. The method used in this study is an Analytical Survey with a crossectional approach. Sampling technique with Purposive Sampling of the number of respondents 40, the data collected were analyzed using Chi Square with the SPSS program version 24. The results of the Chi-Square test with α 0.05 found that age p=0,03, parity p=0,386, pregnancy distance p=0,580, comorbidities p=0,850. From the factors that affect the psychic of the mother who tested positive for COVID-19 such as age, parity, pregnancy distance, and comorbidities. age affects covid-19 positive maternity mothers whose psychics are disturbed.